Prevalence of multi-resistant bacteria, environmental contamination, and routine practices in a public hospital (Research, Society and Development, 2022)
The significant increase in antimicrobial-resistant bacteria is a major public health problem. The Intensive Care Units (ICUs), as they have critically ill patients, are the most susceptible and promoters of hospital infections. Acinetobacter baumannii and Klebsiella pneumoniae are important species that cause hospital infections, associated with resistance mechanisms that make the strains more virulent. The purpose of this article was to perform epidemiological tracking of the most prevalent bacterial strains and seek their involvement with hospital infections in a public hospital in Palmas, Tocantins, Brazil. A retrospective study of nosocomial infections from 2017 to 2019 was carried out. In 2019, screening was carried out on bed surfaces, using a sterile swab. In 2020, suspected cases of hospital infection were registered. The samples were sown in specific media and evaluated the resistance profile. Results: a higher prevalence of A. baumannii was found in Intensive Care Units (70.4%) in the respiratory tract and on surfaces. K. pneumoniae showed a significant increase in the ICU and ICU in 2018 and 2019. Professional practices that could contribute to cross-contamination were observed during collections, with little antisepsis and lack of personal protective equipment being identified. The results reinforce the need to create mechanisms for improvement and continuing education for professionals, as well as effective antisepsis processes, and creating outbreak investigation strategies.